Bilateral Primary Breast Cancer With Discordance in Molecular Subtypes: A Case Report - Yingying Rao; Qian Zhan; Hengyu Li (International Journal of Breast Cancer, 2025)
Molecular subtype is a crucial prognostic factor for bilateral breast cancer and plays a key role in guiding treatment decisions. Several studies have confirmed that the expression patterns of hormone receptor and human epidermal growth factor receptor 2 are generally consistent in synchronous bilateral primary breast cancer. Discordance in the receptor expression status is commonly associated with poorer prognosis in synchronous bilateral breast cancer. However, there is currently limited literature reporting such cases. This article presents a case of synchronous bilateral primary breast cancer with discordant molecular subtypes and reviews relevant literature.